Consumer behaviour trends caused and accelerated by COVID-19 triggering shopping centres' marketing offer adaptation – an integrative approach - Knecht-Tarczewska, Maria (Trendy zachowań konsumentów wywołane i przyspieszone przez COVID-19, skutkujące adaptacją oferty marketingowej centrów handlowych – podejście integracyjne, 2022)
This article aimed to review the previous research on consumer behaviour trends caused and accelerated by the COVID-19 pandemic and shopping centres’ marketing offer adaptation, to propose an integrative model of their relation. Theoretical considerations were undertaken based on the literature review and the results of selected market reports. In these results, six trends in consumer behaviour were distinguished, and changes in the shopping centres’ marketing offer were divided into five service dimensions. This integrative approach was used to develop a conceptual model of such relations. Both researchers and practitioners can benefit from these findings. This article synthesises the results of previous research creating an integrative, conceptual framework reflecting the hypothesised relation between the studied phenomena.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 2, s. 73-89
Keywords: shopping centres; consumer behaviour; COVID-19; centra handlowe; zachowania klientów